Beta‐catenin promotes macrophage‐mediated acute inflammatory response after myocardial infarction. Issue 1 (15th December 2017) - Huang, Ling; Xiang, Mei; Ye, Ping; Zhou, Wei; Chen, Manhua
Abstract: Regulatory mechanisms for acute inflammatory responses post myocardial infarction (MI) have yet to be fully understood. In particular, the mechanisms by which cardiac macrophages modulate MI‐induced myocardial inflammation remains unclear. In this study, using a mouse MI model, we showed that β‐catenin‐mediated signaling was activated in cardiac macrophages post‐MI, especially in Ly‐6C‐positive proinflammatory macrophages. Using a RAW264.7‐based β‐catenin reporter cell line, we confirmed the presence of active β‐catenin and its downstream signaling in cardiac macrophages after MI. Moreover, lentivirus‐mediated inducible expression of constitutively active β‐catenin revealed that β‐catenin plays a role in promoting the inflammatory response by RAW264.7 cells. Depletion of endogenous macrophages and adoptive transfer of active β‐catenin‐expressing RAW264.7 cells resulted in enhancement of acute myocardial inflammation in recipient mice after MI, as demonstrated by elevated levels of lymphocyte infiltrates and increased expression of proinflammatory cytokines. However, infarct volume, myocardial tissue repair, and left ventricle function were not influenced by the expression of active β‐catenin in the adoptive transfer assay. Our research has demonstrated that β‐catenin‐mediated signaling is important for cardiac macrophages to modulate post‐MI inflammatory responses. These findings may be valuable for developing novel therapeutic strategies for MI. Abstract : β‐catenin‐mediated signal pathway is activated in Ly‐6C‐positive cardiac macrophages post myocardial infarction. Active β‐catenin promotes the inflammatory response of macrophages, and subsequently aggravates acute myocardial inflammation post myocardial infarction.